# Algebraic Expressions| Worksheet Solutions| Class 7

Worksheet solutions for chapter: Algebraic Expressions for class 7 are provided below.

(1) Identify, in the following expressions, terms which are not constants. Give their numerical coefficients:

xy – 1, 2x + 3- y, 5x + 5z

Ans- (2) Identify terms and factors in the expressions given below:

(a) 4x + 5z (b) -ab + 4b

Ans- (3) Classify into monomials, binomials and trinomials.

(a) 7x -9 (b) 5a2 + 3b -9 (c)2p

Ans-

(a) 7x -9   :- Binomial

(b) 5a2 + 3b -9  :- Trinomial

(c) 2p :- Monomial

(4) State whether a given pair of terms is of like or unlike terms.

(a)1,19 (b ) 2x, 3x2(c) ab, 100ab

Ans-

(a)1,19  ;- lIke Terms

(b ) 2x, 3x2 :- Unlike terms

(c) ab,100ab :- Like Terms

(i) 3z – 5, 4z +1

(ii) 2x2 +5, 6 + 3x2

Ans-

(i) 3z – 5, 4z +1

= (3z – 5) + (4z +1)

=3z – 5 +4z +1

=3z +4z -5 + 1

=(3 +4)z – 4

=7z – 4

(ii) 2x2 +5, 6 + 3x2

=(2x2 +5) + (6 + 3x2)

=2x2 + 3x2 +5 +6

=(2 + 5) x2 + 11

= 7 x2 + 11

(6) Subtract:

(i) 6ab from 8ab

(ii) –m2 + 2m +6, 3m – 4m2+9

Ans-

(i) 6ab from 8ab

=8ab – 6ab

=2ab

(ii) –m2 + 2m +6 from  3m – 4m2+9

=(3m – 4m2+9) – (–m2 + 2m +6)

= 3m – 4m2+9 + m2 – 2m – 6

=3m – 2m – 4m2+ m2 +9 – 6

=(3 – 2)m – (4 – 1) m2 +3

=m – 3m2 +3

(7) What should be added to ab +2a + 4 to obtain 2ab -7?

Ans- (8) From the sum of 3x +4xy +5 and 2x – 4xy +5 subtract 4x – 5 +2xy.

Ans- (9) If n = 4, find the value of:

(i) n+11 (ii) 3n -5

Ans-

(i) n +11

Putting n = 4

In n +11, we get

n + 11 = 4 + 11 = 15

(ii) 3n – 5

Putting n= 4

In 3n – 5,we get

3n – 5 = 3 × 4 – 5 = 12 – 5=7

(10) Simplify these expressions and find their values if x=0 and y = 1

(i) 2xy + y –x +2x (ii) 3x – 4xy +2xy -5

Ans-

(i) 2xy + y –x +2x

Simplifying expression:

2xy + y –x +2x

2xy +y –(1 – 2)x

=2xy + y +x

Putting x=0 and y = 1

In 2xy + y –x +2x, we get

2xy + y –x +2x

= 2× 0×1 + 1 – 0 +2 × 0

= 0 +1 -0 + 0

=1

(ii)

3x – 4xy +2xy -5

Simplifying expression:

3x – 4xy +2xy -5

3x – ( 4 – 2)xy -5

=3x – 2xy -5

Putting x=0 and y = 1

In 3x – 4xy +2xy -5, we get

3x – 4xy +2xy -5

= 3×0 – 4× 0× 1 +2 ×0 ×1 – 5

=0 -0+0-5

=-5

Helping Topics

Algebraic Expressions

NCERT Solutions Class 7